Design of a trial to evaluate the impact of clinical pharmacists and community health promoters working with African-Americans and Latinos with Diabetes - Gerber Ben S; Rapacki Lauren; Castillo Amparo; Tilton Jessica; Touchette Daniel R; Mihailescu Dan; Berbaum Michael L; Sharp Lisa K (BMC, 2012)
Abstract Background Given the increasing prevalence of diabetes and the lack of patients reaching recommended therapeutic goals, novel models of team-based care are emerging. These teams typically include a combination of physicians, nurses, case managers, pharmacists, and community-based peer health promoters (HPs). Recent evidence supports the role of pharmacists in diabetes management to improve glycemic control, as they offer expertise in medication management with the ability to collaboratively intensify therapy. However, few studies of pharmacy-based models of care have focused on low income, minority populations that are most in need of intervention. Alternatively, HP interventions have focused largely upon low income minority groups, addressing their unique psychosocial and environmental challenges in diabetes self-care. This study will evaluate the impact of HPs as a complement to pharmacist management in a randomized controlled trial. Methods/Design The primary aim of this randomized trial is to evaluate the effectiveness of clinical pharmacists and HPs on diabetes behaviors (including healthy eating, physical activity, and medication adherence), hemoglobin A1c, blood pressure, and LDL-cholesterol levels. A total of 300 minority patients with uncontrolled diabetes from the University of Illinois Medical Center ambulatory network in Chicago will be randomized to either pharmacist management alone, or pharmacist management plus HP support. After one year, the pharmacist-only group will be intensified by the addition of HP support and maintenance will be assessed by phasing out HP support from the pharmacist plus HP group (crossover design). Outcomes will be evaluated at baseline, 6, 12, and 24 months. In addition, program and healthcare utilization data will be incorporated into cost and cost-effectiveness evaluations of pharmacist management with and without HP support. Discussion The study will evaluate an innovative, integrated approach to chronic disease management in minorities with poorly controlled diabetes. The approach is comprised of clinic-based pharmacists and community-based health promoters collaborating together. They will target patient-level factors (e.g., lack of adherence to lifestyle modification and medications) and provider-level factors (e.g., clinical inertia) that contribute to poor clinical outcomes in diabetes. Importantly, the study design and analytic approach will help determine the differential and combined impact of adherence to lifestyle changes, medication, and intensification on clinical outcomes. Trial registration ClinicalTrials.gov identifier: NCT01498159